2017
DOI: 10.3390/ijms18122516
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer Bioinformatics

Abstract: Aptamers are short nucleic acid sequences capable of specific, high-affinity molecular binding. They are isolated via SELEX (Systematic Evolution of Ligands by Exponential Enrichment), an evolutionary process that involves iterative rounds of selection and amplification before sequencing and aptamer characterization. As aptamers are genetic in nature, bioinformatic approaches have been used to improve both aptamers and their selection. This review will discuss the advancements made in several enclaves of aptam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 118 publications
1
66
0
1
Order By: Relevance
“…The high repeat of a sequence in a cell-SELEX library does not guarantee specificity or affinity toward a receptor. For example, analysis of enriched aptamer libraries by HT sequencing, or Sanger sequencing, revealed that high-affinity sequences do not necessarily appear in high repeats, as determined in several studies 26, 27, 28. Outcompeted molecules in LIGS pools can be divided into three types of DNA ligands: those that specifically outcompeted DNA ligands resulting from specific mAb competition, those weak binding DNA ligands with high off-rates, and those nonspecifically eluted off-target sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The high repeat of a sequence in a cell-SELEX library does not guarantee specificity or affinity toward a receptor. For example, analysis of enriched aptamer libraries by HT sequencing, or Sanger sequencing, revealed that high-affinity sequences do not necessarily appear in high repeats, as determined in several studies 26, 27, 28. Outcompeted molecules in LIGS pools can be divided into three types of DNA ligands: those that specifically outcompeted DNA ligands resulting from specific mAb competition, those weak binding DNA ligands with high off-rates, and those nonspecifically eluted off-target sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most of the modifications aim at the improvement and acceleration of the aptamer selection process [ 12 , 13 ]. In this regard, NGS technologies have contributed substantially in the last years [ 15 , 18 , 19 , 20 , 21 ]. NGS has the potential to completely replace cloning and Sanger sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Although we started with a 60 nt library with 30 random sequences, the selected sequence was only a 41 nt. This sequence is generally thought to be a PCR error when amplified for the next round [21] and is excluded from the candidates. However, this sequence was confirmed extraordinarily, leading us to select it.…”
Section: Discussionmentioning
confidence: 99%